Systematic review on the frequency and quality of reporting patient and public involvement in patient safety research - Sahar Hammoud; Laith Alsabek; Lisa Rogers; Eilish McAuliffe (BMC, 2024)
Abstract Background In recent years, patient and public involvement (PPI) in research has significantly increased; however, the reporting of PPI remains poor. The Guidance for Reporting Involvement of Patients and the Public (GRIPP2) was developed to enhance the quality and consistency of PPI reporting. The objective of this systematic review is to identify the frequency and quality of PPI reporting in patient safety (PS) research using the GRIPP2 checklist. Methods Searches were performed in Ovid MEDLINE, EMBASE, PsycINFO, and CINAHL from 2018 to December, 2023. Studies on PPI in PS research were included. We included empirical qualitative, quantitative, mixed methods, and case studies. Only articles published in peer-reviewed journals in English were included. The quality of PPI reporting was assessed using the short form of the (GRIPP2-SF) checklist. Results A total of 8561 studies were retrieved from database searches, updates, and reference checks, of which 82 met the eligibility criteria and were included in this review. Major PS topics were related to medication safety, general PS, and fall prevention. Patient representatives, advocates, patient advisory groups, patients, service users, and health consumers were the most involved. The main involvement across the studies was in commenting on or developing research materials. Only 6.1% (n = 5) of the studies reported PPI as per the GRIPP2 checklist. Regarding the quality of reporting following the GRIPP2-SF criteria, our findings show sub-optimal reporting mainly due to failures in: critically reflecting on PPI in the study; reporting the aim of PPI in the study; and reporting the extent to which PPI influenced the study overall. Conclusions Our review shows a low frequency of PPI reporting in PS research using the GRIPP2 checklist. Furthermore, it reveals a sub-optimal quality in PPI reporting following GRIPP2-SF items. Researchers, funders, publishers, and journals need to promote consistent and transparent PPI reporting following internationally developed reporting guidelines such as the GRIPP2. Evidence-based guidelines for reporting PPI should be encouraged and supported as it helps future researchers to plan and report PPI more effectively. Trial registration The review protocol is registered with PROSPERO (CRD42023450715).